Implementasi Program Sekolah Ramah Anak di SD Muhammadiyah Ambarbinangun Kasihan Bantul - Yuliana Intan Felany; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Child-Friendly School (CFS) Program at SD Muhammadiyah Ambarbinangun Kasihan Bantul based on the six CFS components. Using a descriptive qualitative approach, the research involved the principal, the coordinator of the CFS implementation team, teachers, and student representatives. Data were collected through observation, interviews, and documentation, then analyzed through data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings show that the implementation of the CFS Program has been carried out effectively. In the policy component, the school demonstrates strong commitment through written regulations such as an Anti-Violence Decree, a Violence Prevention and Handling Team, and a CFS Implementation Team. Positive discipline is practiced, reporting mechanisms are available, and efforts to prevent violence and school dropout are implemented. In the learning process component, instruction is conducted in a supportive manner and child-friendly classroom environments are encouraged. In the component of educators and education personnel, the principal and teachers have received training on children’s rights and have shared the knowledge with all school members through a CFS Working Group. Regarding facilities and infrastructure, most school facilities are safe and comfortable, although ramps, disability-friendly toilets, and CCTV have not yet been provided. In the child participation component, students are involved in school activities, the formulation of school rules, the selection of extracurricular options, and participation in the CFS Implementation Team. Collaboration with parents, community institutions, the business sector, stakeholders, and alumni is also established.